STUDENT RESPONSE TO ONLINE LEARNING IN MATHEMATICS MATERIAL DIVISION USING BRIDGE CARD MEDIA - sahrani Danur Kusuma Abdillah; Kusnaningsih Kusnaningsih; Rika Wulandari (Citra Dharma Cindekia, 2022)
Learning mathematics is an important aspect for students in everyday life. For that we need a very good method of learning mathematics so that students feel fun in learning takes place. This article aims to provide an overview of the effectiveness of the application of playing card learning media in mathematics during online learning at Banyuajuh 2 elementary school. This research is a mixed quantitative and qualitative research (mix method). Data were initially collected using quantitative methods followed by qualitative methods. The target population of this study were students at Banyuajuh 2 Kamal elementary school. In addition, the samples used by the researcher were 2 elementary school students in grades 3, 6 and 4. The instruments used by researchers are interviews and observation and documentation. The results of the study show that during online learning the teacher has used various media to be able to increase students' motivation and understanding of the mathematics subject in the distribution material. However, the media that is most popular and increases student motivation and understanding is playing cards. As many as 88% of students stated that they preferred playing card media compared to other media during online learning. This makes their motivation and understanding of the division material in mathematics subjects greater. From the results of this study it can be concluded that playing card media is effective in increasing students' motivation and understanding in the distribution of mathematics subject matter